2011IEEE 10th International Conference on Trust, Security and Privacy in Computing and Communications 2011
DOI: 10.1109/trustcom.2011.144
|View full text |Cite
|
Sign up to set email alerts
|

On Partitioned Scheduling of Fixed-Priority Mixed-Criticality Task Sets

Abstract: Abstract-Mixed-criticality real-time systems, where tasks may be associated with different criticality and assurance levels, have attracted much attention in the recent past. In this paper, we consider partitioning-based multiprocessor scheduling of mixedcriticality real-time task sets. Guaranteeing feasibility in this setting is shown to be NP-Hard. With a focus on fixed-priority preemptive scheduling on each processor, we identify the two main aspects of the problem, namely the task allocation and priority a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 19 publications
(51 reference statements)
0
44
0
2
Order By: Relevance
“…• DU-RMS: a scheduling algorithm from [20] in which the workloads are arranged in descending order based on their utilization and higher priorities are allocated to workloads with lower inter-arrival time (i.e., Decreasing Utilization-Rate Monotonic Scheduling);…”
Section: Experiments and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…• DU-RMS: a scheduling algorithm from [20] in which the workloads are arranged in descending order based on their utilization and higher priorities are allocated to workloads with lower inter-arrival time (i.e., Decreasing Utilization-Rate Monotonic Scheduling);…”
Section: Experiments and Resultsmentioning
confidence: 99%
“…They proposed an SIL-based WCET for the tasks and a dispatching algorithm for mapping tasks to processor [20]. In order to explore both general and criticality mode change protocols, Burns surveyed the pessimistic assumptions of high criticality tasks in the higher criticality modes [21].…”
Section: Related Workmentioning
confidence: 99%
“…This work differs from the approach we consider in this paper in that it assumes the existence of a run-time mechanism that terminates tasks of a particular criticality level if the criticality level attributed to the behaviour of the system exceeds that level. In Kelly et al (2011), we explored the partitioned scheduling of mixed-criticality systems, considering the relative importance of the two key dimensions of this problem, namely task allocation and priority assignment.…”
Section: Related Workmentioning
confidence: 99%
“…In Kelly et al (2011), we explored the use of Audsley's algorithm in the partitioned scheduling of mixed-criticality task sets where it was applied following the allocation step for the scheduling of the subset of tasks allocated to each processor. We found that it offered a significant performance gain over RM priority assignment in this setting.…”
Section: Audsley's Algorithmmentioning
confidence: 99%
See 1 more Smart Citation